Analysis of 5G Signal Quality on 2100 MHz and 2300 MHz Frequencies Based on RSRQ, RSRP, and SNR Parameters - Dito Tobmuti; Eriwien Christianto (P3M Politeknik Negeri Bengkalis, 2025)
Abstract—The rapid growth of cellular communication technology necessitates fast and stable internet connections. This research addresses the limited studies on 5G network performance in Surakarta City, which is experiencing increased demand for reliable internet access. We employed a drive test method using the G-Net Track Pro application to measure 5G signal quality based on RSRP, RSRQ, and SINR parameters on 2100 MHz and 2300 MHz frequencies. The study aimed to compare signal quality between Telkomsel and XL across four key locations in Surakarta. Results indicate that Telkomsel generally shows excellent RSRP, while XL also provides competitive signal strength in specific areas. RSRQ for both operators consistently falls into the